The Role of Work-Life Balance in Mediating Leadership Style on the Performance of Employees of the Morowali Regency Population and Civil Registration Office - Mohammad Ega Nugraha; Armawati; Muhammad Riswandi Palawa; Nurdiana; Selvi Sulistiani; Abdul Rahman (Jurnal Sinar Manajemen, 2025)
This study aims to analyse how leadership style affects employee performance through work-life balance as a mediating variable. The research subjects are employees of the Morowali Regency Population and Civil Registration Office. The method used is a quantitative approach with data analysis using SmartPLS. The results of the study are expected to show that leadership style has a significant influence on employee performance, both directly and through the mediation of work-life balance. With good work-life balance, employees are expected to be more productive and effective in performing their duties, as they are able to balance work and personal life. Additionally, this study contributes to human resource management, particularly in enhancing performance through an approach that prioritises work-life balance and effective leadership. It is hoped that this research will provide insights for department leaders to improve leadership styles that support work-life balance, thereby achieving optimal performance